Disassembly activity of actin depolymerization factor (ADF) is associated with distinct cellular processes in apicomplexan parasites. - Haase,S; Zimmermann,D; Olshina,MA; Wilkinson,M; Fisher,F; Tan,YH; Stewart,RJ; Tonkin,CJ; Wong,W; Kovar,DR; Baum,J (Molecular Biology of the Cell, 2015)
Proteins of the actin depolymerizing factor (ADF)/cofilin family have been shown to be crucial for the motility and survival of apicomplexan parasites. However, the mechanisms by which ADF proteins fulfill their function remains poorly understood. In this study we sought to investigate the comparative activities of ADF proteins from Toxoplasma gondii and Plasmodium falciparum, the human malaria parasite, using a conditional T. gondii ADF-knockout line complemented with ADF variants from either species. We show that P. falciparum ADF1 can fully restore native TgADF activity, demonstrating functional conservation between parasites. Strikingly, mutation of a key basic residue (Lys(72)), previously implicated in disassembly in PfADF1, had no detectable phenotypic effect on parasite growth, motility or development. In contrast, organelle segregation was severely impaired when complementing with a TgADF mutant lacking the corresponding residue (Lys(68)). Biochemical analyses of each ADF protein confirmed the reduced ability of lysine mutants to mediate actin depolymerization via filament disassembly though not severing, in contrast to previous reports. These data suggest that actin filament disassembly is essential for apicomplexan parasite development but not for motility as well as pointing to genus-specific coevolution between ADF proteins and their native actin.